Traumatic brain injury in child: reporting a clinical case - Afonso, Carla; Interno do Internato Complementar de MFR - Serviço de Reabilitação Pediátrica e Desenvolvimento, Centro de Medicina de Reabilitação, Alcoitão, Portugal (2013)
Traumatic brain injury (TBI), traumatic injuries to the brain, also called intracranial injury, or simply head injury, occurs when a sudden trauma causes brain damage. TBI can result from a closed head injury or a penetrating head injury and is one of two subsets of acquired brain injury (ABI). TBI is a major public health problem, especially among males ages 15 to 24, and among elderly people of both sexes 75 years and older. Children aged 5 and younger are also at high risk for TBI.Males account for two thirds of childhood and adolescent head trauma patients. Half of all TBIs are due to transportation accidents involving automobiles, motorcycles, bicycles, and pedestrians. Approximately 20% of TBIs are due to violence, such as firearm assaults and child abuse, and about 3% are due to sports injuries. Material and methods: The authors describe a case of a young boy of 17 years old that by the age of 8 was hit by a football beacon that caused a severe brain injury. He is regularly followed in consultations in the Pediatric and Development Rehabilitation Service – Centro de Medicina de Reablitação Alcoitão. The authors will describe the effects of TBI in this particular case, either cognitive problems, sensory, emotional as physical problems. Conclusions: Rehabilitation is an important and critical part of the recovery process for a TBI patient. The overall goal of rehabilitation after a TBI is to improve the patient’s ability to function at home and in society in the face of the residual effects of the injury, which may be complex and multifaceted. Patients will often have problems in the areas of general cognition, social cognition/awareness, behavior and emotional regulation that present significant challenges, in terms of being able to resume expected social roles. This case is an example of how the neuro-phsychological sequelae were disabling in the child’s life, specially in cognition areas. Póster Científico apresentado no VII World Congress on Brain Injury – Lisboa, 9 a 12 de Maio 2008